Genome-Wide Identification and Comparative Analysis of WRKY Transcription Factors Related to Momilactone Biosynthesis in Calohypnum plumiforme - Wang, Yao; Zhu, Ruiyan; Shi, Min; Huang, Qikai; Zhang, Siwei; Kai, Guoyin; Guo, Shuiliang (Frontiers in Ecology and Evolution, 2022)
Momilactones are diterpenoid phytoalexins with allelopathic functions, which have been found in the widely distributed bryophyte Calohypnum plumiforme. Clustered genes containing CpDTC1/HpDTC1, CpCYP970A14, CpCYP964A1, and CpMAS are involved in momilactone biosynthesis. Besides, momilactone concentration in C. plumiforme is affected by heavy metal treatment such as CuCl2. However, transcription factors which might regulate momilactone biosynthesis are unclear. WRKY transcription factors (TFs) regulate phytoalexins biosynthesis in many plant species. In this study, a systematic analysis of the WRKY TFs was performed according to the C. plumiforme genome. A total of 19 CpWRKY genes were identified and categorized into five subgroups based on their phylogenetic relationship. Conserved domain and motif analysis suggested that the WRKY domain was highly conserved, but there were some variations. Cis-acting elements and binding sites analysis implied that CpWRKY genes might be induced by stress and further regulate the biosynthesis of momilactones. Our study lays a foundation for further functional characterization of the candidate CpWRKY genes involved in the regulation of momilactone biosynthesis, and provides new strategies for increasing momilactone production.